ANALISIS PENGEMBANGAN POTENSI EKONOMI LOKAL UNTUK MENGUATKAN DAYA SAING DAERAH DI KABUPATEN GRESIK - Nailatul Husna (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2013)
Abstract Regional development need attention to regional potential, which is done by examining the GDP to notice any potential base and non-base in order to optimize development results in order to obtain a high level of welfare. If the government want their regency have competitiveness, development programs should be set off from primary economic potential. This research aims analyze the potential development of local economy in Gresik Regency. As well as the efforts of local authorities in favour of Gresik Regency development of primary local economic potential to strengthen the competitiveness of the region. The approach used is quantitative descriptive, with the method of Location Quotient and Shift Share. The results of this research say that most potential sector that developed in Gresik Regency that is, manufacturing industry sector; electricity, gas and water supply; as well as mining and quarrying sector. While Government support Gresik as seen Regional Long Term Development Plan (RLTDP) and Regional Medium Term Development Plan (RMTDP) also in Regional Budget Revenue and Expenditure (RBRE) allocation. tend to prioritize on a sector that is less like a potential trade, hotels and restaurants; as well as agriculture. Thus, the Government of Gresik Regency to prioritising the development programs and allocating budget on primary sector. Keywords : Base Potential,Government Efforts, Regional Competitive Abstrak Pembangunan daerah perlu memperhatikan potensi daerah, yang dilakukan dengan menelaah PDRB untuk melihat adanya potensi basis dan non basis dalam rangka mengoptimalkan hasil pembangunan guna mendapatkan tingkat kesejahteraan yang tinggi. Jika pemerintah menginginkan daerahnya berdaya saing, maka program pembangunannya harus berangkat dari pengembangan potensi ekonomi unggulannya. Penelitian ini bertujuan menganalisis pengembangan potensi ekonomi lokal di Kabupaten Gresik. Serta Upaya pemerintah daerah Kabupaten Gresik dalam mendukung pengembangan potensi ekonomi lokal unggulan untuk memperkuat daya saing daerah. Pendekatan yang digunakan adalah kuantitatif deskriptif, dengan metode Locaion Quotient dan Shift Share. Hasil dari penelitian ini menyebutkan bahwa sektor yang paling potensial dikembangkan di Kabupaten Gresik yaitu, sektor industri pengolahan; listrik, gas, dan air bersih; serta sektor pertambangan dan penggalian. Sedangkan dukungan Pemerintah Kabupaten Gresik dilihat dari RPJPD danRPJMD serta alokasi APBD cenderung memprioritaskan pada sektor yang kurang potensial seperti perdagangan, hotel, dan restoran; serta pertanian. Maka, pemerintah Kabupaten Gresik perlu memprioritas program pembangunan maupun pengalokasian anggarannya pada sektor unggulan. Â Kata Kunci : Potensi Basis/Unggulan, Upaya Pemerintah, Daya Saing Daerah